The Influence of Organizational Culture, Teacher and Staff Involvement, and Leadership on the Performance of Teachers and Staff at SMA Dwi Warna - Solihin, Agung; Tarmizi, Achmad (Jurnal Multidisiplin Sahombu, 2025)
This study examines the influence of organizational culture, teacher and staff involvement, and leadership on the performance of teachers and staff at SMA Dwi Warna. Employing a quantitative approach with a saturated sampling method, data were collected through structured questionnaires and analyzed using multiple regression. The findings reveal that organizational culture, involvement, and leadership each contribute positively to enhancing performance, both individually and collectively. A supportive organizational culture fosters a shared vision and professional collaboration, while active involvement encourages commitment and accountability. Furthermore, effective leadership provides clear direction, motivation, and a conducive work environment. The results underscore the importance of integrating cultural values, participatory engagement, and leadership practices to improve overall performance. These insights offer practical implications for educational institutions seeking to strengthen human resource management and achieve sustainable performance growth.